Porous hard carbon negative material, preparation method thereof and sodium ion battery
Patent Information
- Application Number
- CN202611268998.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]为了解决现有技术中硬炭负极材料比容量较低的问题,本发明提供一种多孔硬炭负极材料的制备方法,该制备方法通过预掺杂钠弱化碳层间作用力、构建碳空位,拓宽碳层间距、提升钠离子吸附位点,提高比容量,解决了现有技术中硬炭负极材料比容量较低的问题
本发明提供的多孔硬炭负极材料的制备方法,含钠硫化合物在前驱体阶段已经与硬炭前驱体充分混合,并通过柠檬酸辅助结合形成均匀分布结构;含钠硫化合物引入钠元素,通过预掺杂钠弱化碳层间作用力、构建碳空位,Na嵌入无定形碳骨架,削弱C-C层间作用力、制造碳本征空位,拓宽碳层间距、提升Na+吸附位点,提高比容量;同时,钠掺杂引导薄、无机富集稳定SEI膜,骨架原位Na提前锚定界面,充放电时直接诱导薄、高NaF占比SEI,减少不可逆钠消耗,提升首次库伦效率;此外,Na-S二元原位共掺,硫调控闭孔结构、钠调控电子能带,双机制协同提升硬炭动力学。
Smart Images

Figure REF-OBJ-1787205151009-000001
Abstract
Description
Technical Field
[0001] This invention relates to the field of hard carbon materials technology, and in particular to a porous hard carbon anode material, its preparation method, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries, due to the abundance and low cost of sodium resources and their similar working principle to lithium-ion batteries, are considered one of the most promising supplementary or alternative solutions for lithium-ion batteries in the field of large-scale energy storage. The anode material is a key factor determining the electrochemical performance of sodium-ion batteries. Currently, hard carbon materials, with their unique short-range ordered, long-range disordered layered structure, large graphite interlayer spacing, and abundant nanopores, are widely recognized as the most commercially promising anode material for sodium-ion batteries.
[0003] Theoretically, the sodium storage mechanism of hard carbon mainly includes three modes: defect site adsorption, carbon intercalation, and nanopore filling. The three-stage model of "adsorption-intercalation-pore filling" has been widely accepted to explain its charge-discharge behavior. However, compared with the mature application of graphite anodes in lithium-ion batteries, hard carbon anodes still face severe challenges in sodium-ion batteries. Because the radius of sodium ions is much larger than that of lithium ions, the insertion / extraction kinetics of sodium ions in carbon layers are slow, resulting in generally low reversible specific capacity of the material, which seriously restricts the further improvement of the energy density of sodium-ion batteries and their industrialization process. Summary of the Invention
[0004] To address the issue of low specific capacity in existing hard carbon anode materials, this invention provides a method for preparing porous hard carbon anode materials. This method weakens the interlayer forces of carbon by pre-doping with sodium, constructs carbon vacancies, widens the carbon interlayer spacing, and increases sodium ion adsorption sites, thereby improving the specific capacity and solving the problem of low specific capacity in existing hard carbon anode materials.
[0005] The technical solution adopted by this invention to solve its technical problem is: A method for preparing a porous hard carbon anode material includes the following steps: The hard carbon precursor, sodium-sulfur compound and citric acid were dissolved in deionized water to obtain a mixed solution; Under constant temperature water bath conditions of 60-70℃, ammonia water was added to the mixed solution to adjust the pH to 9-11, the reaction was stirred, and then dried to obtain the Na-S co-doped precursor. Under an inert atmosphere, the Na-S co-doped precursor is heated to 350-650℃ and held for a period of time, then heated to 1200-1500℃ and held for a period of time to obtain a porous hard carbon anode material.
[0006] Optionally, the hard carbon precursor is selected from at least one of resin hard carbon precursor, biomass hard carbon precursor, coal-based hard carbon precursor, and pitch-based hard carbon precursor.
[0007] Optionally, the resin hard carbon precursor is selected from at least one of phenolic resin and furan resin.
[0008] Optionally, the biomass hard char precursor is selected from at least one of wood and fruit shells.
[0009] Optionally, the sodium-containing sulfur compound is selected from at least one of organic sodium-containing sulfides and inorganic sodium-containing sulfides.
[0010] Optionally, the organic sodium sulfide is selected from at least one of sodium lignosulfonate, sodium p-toluenesulfonate, sodium methpropylenesulfonate, sodium benzenesulfonate, sodium dodecylbenzenesulfonate, and sodium naphthalenesulfonate.
[0011] Optionally, the inorganic sodium-containing sulfide is selected from at least one of sodium sulfide, sodium polysulfide, sodium hydrosulfide, sodium thiosulfate, and sodium sulfite.
[0012] Optionally, the mass ratio of the hard carbon precursor, the sodium-sulfur compound, and the citric acid is (20-35):(40-60):(3-8).
[0013] Another object of the present invention is to provide a porous hard carbon anode material, which is prepared by the method described above for preparing porous hard carbon anode materials.
[0014] Another object of the present invention is to provide a sodium-ion battery comprising the porous hard carbon anode material as described above.
[0015] The beneficial effects of this invention are: The method for preparing porous hard carbon anode material provided by this invention involves fully mixing a sodium-sulfur compound with the hard carbon precursor during the precursor stage, and forming a uniformly distributed structure through citric acid-assisted bonding. The sodium-sulfur compound introduces sodium, which weakens the carbon interlayer forces and creates carbon vacancies through pre-doping. Na is then embedded into the amorphous carbon framework, further weakening the C / C interlayer forces, creating intrinsic carbon vacancies, widening the carbon interlayer spacing, and enhancing the Na content. + Adsorption sites are improved to increase specific capacity; at the same time, sodium doping guides the thin, inorganic enrichment and stabilization of the SEI film, and the in-situ Na framework anchors the interface in advance, directly inducing a thin, high NaF ratio SEI during charging and discharging, reducing irreversible sodium consumption and improving the first coulombic efficiency; in addition, Na-S binary in-situ co-doping, sulfur regulates the closed-pore structure and sodium regulates the electronic energy band, and the two mechanisms synergistically improve the hard carbon kinetics. Detailed Implementation
[0016] The present invention will now be described in further detail. The embodiments described below are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0017] To address the problem of low specific capacity in existing hard carbon anode materials, this invention provides a method for preparing porous hard carbon anode materials, which includes the following steps: S1: Dissolve the hard carbon precursor, sodium-sulfur compound and citric acid in deionized water to obtain a mixed solution; This invention introduces a sodium-sulfur compound as a common source of Na and S elements, achieving simultaneous introduction of Na / S elements. This allows Na and S to coexist at the molecular level, thus enabling the synchronous distribution of Na and S sites during the precursor stage. Compared to the traditional doping method of introducing sodium and sulfur sources separately, this invention avoids the problems of local Na enrichment and local S deficiency by simultaneously introducing Na and S elements through a sodium-sulfur compound. Preferably, in this step, the mass ratio of the total mass of the hard carbon precursor, the sodium-sulfur compound, and citric acid to the mass of deionized water is 1:(1-5).
[0018] S2: Under constant temperature water bath conditions of 60-70℃, ammonia water is added to the mixed solution to adjust the pH to 9-11, the reaction is stirred, preferably for 2-8 hours, and then dried to obtain the Na-S co-doped precursor. Preferably, the drying process in this step is to dry by blowing air at 80-120℃, and further preferably, after drying, the product is pulverized to a particle size of 5-8μm to obtain the Na-S co-doped precursor; In this step, citric acid acts as a crosslinking agent, undergoing esterification crosslinking between its carboxyl groups and the hydroxyl groups on the hard carbon precursor to construct a three-dimensional crosslinking network. This anchors sodium and sulfur compounds into the crosslinking network, achieving the dispersion of sodium and sulfur elements. Furthermore, the introduction of ammonia water provides a weakly alkaline environment, which helps promote the copolymerization and crosslinking reaction between the hard carbon precursor and the sodium and sulfur compounds, activates functional groups, increases the crosslinking reaction rate, and maintains the reaction conditions at pH=9-11. As a result, the following reaction occurs in this step: the carboxyl groups of citric acid undergo esterification crosslinking with the hydroxyl groups of the hard carbon precursor, while the hard carbon precursor and the sodium and sulfur compounds undergo copolymerization and condensation reaction. The Na and S functional groups are covalently / coordinated and anchored into the organic crosslinking network, thereby jointly constructing a Na-S co-doped precursor with a uniform distribution of sodium and sulfur elements.
[0019] S3: Under an inert atmosphere, the Na-S co-doped precursor is heated to 350-650℃ and held for 1-6 hours, then heated to 1200-1500℃ and held for 1-6 hours to obtain a porous hard carbon anode material. The preferred inert atmosphere is nitrogen or argon; and the preferred heating rate in this step is 1-10℃ / min. In this step, during the heat treatment stage at 350-650℃, S atoms are embedded into the carbon framework, while Na atoms initially replace carbon edge sites, generating a large number of carbon vacancies and weakening local C-C bonds. The small molecule gas generated by decomposition constructs submicron channels in situ, and some channels form closed pores during the high-temperature treatment stage. Further, during the heat treatment stage at 1200-1500℃, Na atoms are embedded into the carbon layer lattice, widening the carbon layer spacing.
[0020] The method for preparing porous hard carbon anode material provided by this invention involves fully mixing a sodium-sulfur compound with the hard carbon precursor during the precursor stage, and forming a uniformly distributed structure through citric acid-assisted bonding. The sodium-sulfur compound introduces sodium, which weakens the carbon interlayer forces and creates carbon vacancies through pre-doping. Na is then embedded into the amorphous carbon framework, further weakening the C / C interlayer forces, creating intrinsic carbon vacancies, widening the carbon interlayer spacing, and enhancing the Na content. + Adsorption sites are improved to increase specific capacity; at the same time, sodium doping guides the thin, inorganic enrichment and stabilization of the SEI film, and the in-situ Na framework anchors the interface in advance, directly inducing a thin, high NaF ratio SEI during charging and discharging, reducing irreversible sodium consumption and improving the first coulombic efficiency; in addition, Na-S binary in-situ co-doping, sulfur regulates the closed-pore structure and sodium regulates the electronic energy band, and the two mechanisms synergistically improve the hard carbon kinetics.
[0021] Specifically, the preferred hard carbon precursor of the present invention is selected from at least one of resin hard carbon precursor, biomass hard carbon precursor, coal-based hard carbon precursor, and pitch-based hard carbon precursor.
[0022] Furthermore, the resin hard carbon precursor of the present invention is preferably selected from at least one of phenolic resin and furan resin; the biomass hard carbon precursor is preferably selected from at least one of wood and nutshell.
[0023] The sodium-containing sulfur compound of the present invention is preferably selected from at least one of organic sodium-containing sulfides and inorganic sodium-containing sulfides.
[0024] This invention uses sodium-sulfur compounds as a common source of Na and S elements. Its core purpose is to achieve the simultaneous introduction of sodium and sulfur elements using the same chemical system, avoiding the problem of uneven spatial distribution of elements caused by adding sodium and sulfur sources separately in traditional methods. Furthermore, in the preparation of hard carbon materials, Na and S elements have different structural regulation effects. Therefore, by providing Na and S elements simultaneously through sodium-sulfur compounds, the two elements can produce a synergistic regulatory effect during the carbonization process.
[0025] In traditional hard carbon modification processes, adding sodium salt and sulfur powder separately typically presents the following problems: sodium salt is prone to migration and aggregation during drying; the contact area between sulfur powder and the carbon precursor is limited; and sulfur is easily lost through volatilization during high-temperature treatment. This invention, however, uses sodium-sulfur compounds, allowing Na and S elements to coexist at the molecular scale. During subsequent carbonization, the sodium-sulfur structure thermally decomposes, and sodium and sulfur elements simultaneously enter the carbon network, forming a Na / S co-doped hard carbon structure. This structure helps avoid the problems of excessive local structural defects or uncontrolled pore structure caused by single-element doping.
[0026] Specifically, the present invention preferably selects at least one of sodium lignosulfonate, sodium p-toluenesulfonate, sodium methpropylenesulfonate, sodium benzenesulfonate, sodium dodecylbenzenesulfonate, and sodium naphthalenesulfonate; the above-mentioned sodium lignosulfonate has an organic carbon chain or aromatic structure and can be used as a sulfur source, sodium source and auxiliary carbon source at the same time.
[0027] The inorganic sodium-containing sulfide of this invention is preferably selected from at least one of sodium sulfide, sodium polysulfide, sodium hydrosulfide, sodium thiosulfate, and sodium sulfite; the inorganic sodium-containing sulfide has the characteristics of high Na content and sufficient sulfur release.
[0028] The present invention preferably uses a mass ratio of (20-35):(40-60):(3-8) for hard carbon precursor, sodium-sulfur compound and citric acid. This allows the hard carbon precursor to provide a continuous carbon network, the sodium-sulfur compound to provide Na / S structure regulation, and the citric acid to promote uniform bonding and pore structure regulation. Thus, a three-in-one synergistic system of carbon skeleton construction, element doping and structure regulation is formed, ultimately obtaining a porous hard carbon anode material with large interlayer spacing, abundant defects, reasonable pore size distribution and high structural stability.
[0029] Another object of the present invention is to provide a porous hard carbon anode material, which is prepared by the method for preparing porous hard carbon anode materials as described above.
[0030] The porous hard carbon anode material provided by this invention involves the thorough mixing of a sodium-sulfur compound with the hard carbon precursor during the precursor stage, followed by citric acid-assisted bonding to form a uniformly distributed structure. The sodium-sulfur compound introduces sodium, which weakens the carbon interlayer forces and creates carbon vacancies through pre-doping. Na embedding into the amorphous carbon framework further weakens the C / C interlayer forces, creates intrinsic carbon vacancies, widens the carbon interlayer spacing, and enhances Na content. + Adsorption sites are improved to increase specific capacity; at the same time, sodium doping guides the thin, inorganic enrichment and stabilization of the SEI film, and the in-situ Na framework anchors the interface in advance, directly inducing a thin, high NaF ratio SEI during charging and discharging, reducing irreversible sodium consumption and improving the first coulombic efficiency; in addition, Na-S binary in-situ co-doping, sulfur regulates the closed-pore structure and sodium regulates the electronic energy band, and the two mechanisms synergistically improve the hard carbon kinetics.
[0031] Another object of the present invention is to provide a sodium-ion battery comprising the porous hard carbon anode material as described above.
[0032] The sodium-ion battery provided by this invention utilizes a negative electrode material prepared by thoroughly mixing a sodium-sulfur compound with a hard carbon precursor during the precursor stage, and forming a uniformly distributed structure with the assistance of citric acid. The sodium-sulfur compound introduces sodium, which weakens the carbon interlayer forces and creates carbon vacancies through pre-doping. Na is then embedded into the amorphous carbon framework, further weakening the C / C interlayer forces, creating intrinsic carbon vacancies, widening the carbon interlayer spacing, and enhancing Na content. + Adsorption sites are improved to increase specific capacity; at the same time, sodium doping guides the thin, inorganic enrichment and stabilization of the SEI film, and the in-situ Na framework anchors the interface in advance, directly inducing a thin, high NaF ratio SEI during charging and discharging, reducing irreversible sodium consumption and improving the first coulombic efficiency; in addition, Na-S binary in-situ co-doping, sulfur regulates the closed-pore structure and sodium regulates the electronic energy band, and the two mechanisms synergistically improve the hard carbon kinetics.
[0033] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.
[0034] Example 1
[0035] This embodiment provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 30g of phenolic resin powder, 50g of sodium lignosulfonate and 5g of citric acid in 500mL of deionized water and stir at 500 rpm for 2 h to obtain a mixed solution; S2: Heat to 65℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 65℃, adjust pH=10, stir for 3h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 500℃ at a heating rate of 3℃ / min and held for 3h. Then, the temperature was further increased to 1400℃ and held for 3h to obtain a porous hard carbon anode material.
[0036] Example 2
[0037] This embodiment provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 20g of phenolic resin powder, 40g of sodium lignosulfonate, and 3g of citric acid in 500mL of deionized water and stir at 500 rpm for 2 hours to obtain a mixed solution. S2: Heat to 60℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 60℃, adjust pH=10, stir for 8h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 350℃ at a heating rate of 3℃ / min and held for 6h. Then, the temperature was further increased to 1200℃ and held for 6h to obtain a porous hard carbon anode material.
[0038] Example 3
[0039] This embodiment provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 35g of phenolic resin powder, 60g of sodium lignosulfonate, and 8g of citric acid in 500mL of deionized water and stir at 500 rpm for 2 hours to obtain a mixed solution. S2: Heat to 70℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 70℃, adjust pH=10, stir for 2h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 650℃ at a heating rate of 5℃ / min and held for 1h. Then, the temperature was further increased to 1500℃ and held for 1h to obtain a porous hard carbon anode material.
[0040] Example 4
[0041] This embodiment provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Disperse 30g coconut shell powder, 50g sodium lignosulfonate and 5g citric acid in 500mL deionized water and stir at 500rpm for 2 hours to obtain a mixed slurry; S2: Heat to 65℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 65℃, adjust pH=10, stir for 3h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 500℃ at a heating rate of 3℃ / min and held for 3h. Then, the temperature was further increased to 1350℃ and held for 3h to obtain a porous hard carbon anode material.
[0042] Example 5
[0043] This embodiment provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 30g of phenolic resin powder, 50g of sodium sulfide, and 5g of citric acid in 500mL of deionized water and stir at 500 rpm for 2 hours to obtain a mixed solution. S2: Heat to 65℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 65℃, adjust pH=10, stir for 3h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 500℃ at a heating rate of 3℃ / min and held for 3h. Then, the temperature was further increased to 1400℃ and held for 3h to obtain a porous hard carbon anode material.
[0044] Each comparative example in this invention is compared with Example 1.
[0045] Comparative Example 1 This comparative example provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 30g of phenolic resin powder and 50g of sodium lignosulfonate in 500mL of deionized water and stir at 500 rpm for 2 hours to obtain a mixed solution; S2: Heat to 65℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 65℃, adjust pH=10, stir for 3h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 500℃ at a heating rate of 3℃ / min and held for 3h. Then, the temperature was further increased to 1400℃ and held for 3h to obtain a porous hard carbon anode material.
[0046] Comparative Example 2 This comparative example provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 30g of phenolic resin powder, 50g of sodium lignosulfonate and 5g of citric acid in 500mL of deionized water and stir at 500 rpm for 2 h to obtain a mixed solution; S2: Heat to 65℃, stir for 3 hours in a constant temperature water bath at 65℃, then dry in a forced air at 80℃ for 12 hours and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 500℃ at a heating rate of 3℃ / min and held for 3h. Then, the temperature was further increased to 1400℃ and held for 3h to obtain a porous hard carbon anode material.
[0047] Comparative Example 3 This comparative example provides a method for preparing a porous hard carbon anode material, which includes the following steps: S1: Dissolve 30g of phenolic resin powder, 50g of sodium lignosulfonate and 5g of citric acid in 500mL of deionized water and stir at 500 rpm for 2 h to obtain a mixed solution; S2: Heat to 65℃, add 25% ammonia water to the mixed solution under constant temperature water bath conditions at 65℃, adjust pH=10, stir for 3h, then dry in a forced air at 80℃ for 12h, and pulverize to 7μm to obtain Na-S co-doped precursor. S3: Under a nitrogen atmosphere, the Na-S co-doped precursor was heated to 1400℃ at a heating rate of 3℃ / min and held for 3h to obtain a porous hard carbon anode material.
[0048] The electrochemical performance of the hard carbon materials prepared in the above embodiments and comparative examples was evaluated using coin cells. The mass ratio of the electrode slurry was 90:5:5 for active material (hard carbon material): conductive agent (carbon black): binder (polyvinylidene fluoride). An appropriate amount of N-methylpyrrolidone was added to prepare the slurry, which was then coated onto copper foil with a coating thickness of 100 μm. After drying and pressing, the slurry was made into an electrode sheet. Using sodium metal as the counter electrode, a 1 mol L⁻¹ NaPF₆ DEC + EC solution (volume ratio 1:1) as the electrolyte, and glass fiber GF / C as the separator, a 2032 coin cell was assembled.
[0049] The test results are shown in Table 1.
[0050] Table 1
[0051] Sodium-ion batteries prepared from the hard carbon materials in the various embodiments of the present invention all exhibit excellent reversible specific capacity and initial efficiency.
[0052] The difference between Comparative Example 1 and Example 1 is that citric acid was not added. Due to the lack of crosslinking agent and carboxyl groups, the hydroxyl groups on the hard carbon could not be crosslinked through esterification to build a three-dimensional crosslinked network, resulting in the inability of sodium and sulfur elements to be evenly dispersed, and the specific capacity and initial efficiency of the hard carbon were reduced.
[0053] The difference between Comparative Example 2 and Example 1 is that no ammonia was added to adjust the pH value. Because the copolymerization and crosslinking reaction rate between the hard carbon precursor and the sodium sulfur compound is reduced, the Na and S functional groups cannot be anchored into the organic crosslinking network, resulting in a decrease in the specific capacity and first efficiency of the hard carbon.
[0054] The difference between Comparative Example 3 and Example 1 is that no low-temperature heat treatment process was performed. Due to insufficient cross-linking reaction, Na and S were only physically mixed and could not achieve molecular-scale anchoring. The elemental distribution was uneven and prone to agglomeration. The precursor cross-linking network was imperfect, which led to a poor doping effect during subsequent carbonization, and the specific capacity and initial coulombic efficiency of hard carbon both decreased.
[0055] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing a porous hard carbon anode material, characterized in that, Includes the following steps: The hard carbon precursor, sodium-sulfur compound and citric acid were dissolved in deionized water to obtain a mixed solution; Under constant temperature water bath conditions of 60-70℃, ammonia water was added to the mixed solution to adjust the pH to 9-11, the reaction was stirred, and then dried to obtain the Na-S co-doped precursor. Under an inert atmosphere, the Na-S co-doped precursor is heated to 350-650℃ and held for a period of time, then heated to 1200-1500℃ and held for a period of time to obtain a porous hard carbon anode material.
2. The method for preparing the porous hard carbon anode material as described in claim 1, characterized in that, The hard carbon precursor is selected from at least one of resin hard carbon precursor, biomass hard carbon precursor, coal-based hard carbon precursor, and pitch-based hard carbon precursor.
3. The method for preparing porous hard carbon anode material as described in claim 2, characterized in that, The resin hard carbon precursor is selected from at least one of phenolic resin and furan resin.
4. The method for preparing the porous hard carbon anode material as described in claim 2, characterized in that, The biomass hard carbon precursor is selected from at least one of wood and fruit shells.
5. The method for preparing the porous hard carbon anode material as described in claim 1, characterized in that, The sodium-containing sulfur compound is selected from at least one of organic sodium-containing sulfides and inorganic sodium-containing sulfides.
6. The method for preparing the porous hard carbon anode material as described in claim 5, characterized in that, The organic sodium sulfide is selected from at least one of sodium lignosulfonate, sodium p-toluenesulfonate, sodium methacrylate sulfonate, sodium benzenesulfonate, sodium dodecylbenzenesulfonate, and sodium naphthalenesulfonate.
7. The method for preparing the porous hard carbon anode material as described in claim 5, characterized in that, The inorganic sodium sulfide is selected from at least one of sodium sulfide, sodium polysulfide, sodium hydrosulfide, sodium thiosulfate, and sodium sulfite.
8. The method for preparing the porous hard carbon anode material according to any one of claims 1-7, characterized in that, The mass ratio of the hard carbon precursor, the sodium-sulfur compound, and the citric acid is (20-35):(40-60):(3-8).
9. A porous hard carbon anode material, characterized in that, The porous hard carbon anode material is prepared by the method described in any one of claims 1-8.
10. A sodium-ion battery, characterized in that, Including the porous hard carbon anode material as described in claim 9.